IMPLEMENTING CHILD SUPPORT GRANT AND TEENAGE PREGNANCY IN DUNCAN VILLAGE - Msiya, Mgwebi (My University, 2014)
Since its inception, Child Support Grant (CSG) has received mixed reactions from across the spectrum. It has given rise to perceptions that it influences teenage girls to desire to fall pregnant so as to access the grant. This research sought to investigate if there is indeed relationship between the CSG and teenage pregnancy. The study followed a triangulation of methods by using quantitative and qualitative approaches. For quantitative data analysis researcher examined data on teenage pregnancy and uptake of CSG in SA. Using Standard Statistical Technique to analyse data, results show that there has been steady increase of teenage pregnancy in SA and Eastern Cape between 2005 and 2011; however the increase is not attributed to CSG. For qualitative data, researcher conducted in-depth interviews with parents that serve in School-Governing Body and school principals. The researcher used thematic analysis to interpret qualitative data. Results suggest that there is no evidence that links CSG to teenage pregnancy.
MM (P&DM) thesis
Keywords: Social security grants; Child support grants; Teenage pregnancy